2015
DOI: 10.1016/j.neulet.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of worry on sustained attention to emotional stimuli: Evidence from the late positive potential

Abstract: There is preliminary evidence to suggest that worry is associated with dysregulated emotion processing resulting from sustained attention to emotional versus neutral stimuli; however, this hypothesis has not been directly tested in prior research. Therefore, the current study used the event-related late positive potential (LPP) to directly examine if high levels of trait worry moderate sustained attention to emotional versus neutral stimuli. Electroencephalogram data was recorded while twenty-two women passive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Rather, this increased attention to threat may constitute a latent vulnerability factor for future symptoms (McCrory & Viding, 2015;McCrory, Gerin, & Viding, 2017). Consistent with this, hypersensitivity to threat can increase negative affect in response to stressors (Eldar, Ricon, & Bar-Haim, 2008;MacLeod, Rutherford, Campbell, Ebsworthy, & Holker, 2002), and may play a role in the maladaptive coping strategies that characterize affective disorders (e.g., worry and rumination; Burkhouse, Woody, Owens, & Gibb, 2015;Siegle, Steinhauer, Thase, Stenger, & Carter, 2002). Furthermore, evidence suggests that the magnitude of the LPP may be a useful endophenotype for internalizing disorders, indicating that enhanced neural responses to threat may reflect increased risk for first onset or recurrence of symptoms (Kujawa et al, 2016;Speed, Nelson, Auerbach, Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Rather, this increased attention to threat may constitute a latent vulnerability factor for future symptoms (McCrory & Viding, 2015;McCrory, Gerin, & Viding, 2017). Consistent with this, hypersensitivity to threat can increase negative affect in response to stressors (Eldar, Ricon, & Bar-Haim, 2008;MacLeod, Rutherford, Campbell, Ebsworthy, & Holker, 2002), and may play a role in the maladaptive coping strategies that characterize affective disorders (e.g., worry and rumination; Burkhouse, Woody, Owens, & Gibb, 2015;Siegle, Steinhauer, Thase, Stenger, & Carter, 2002). Furthermore, evidence suggests that the magnitude of the LPP may be a useful endophenotype for internalizing disorders, indicating that enhanced neural responses to threat may reflect increased risk for first onset or recurrence of symptoms (Kujawa et al, 2016;Speed, Nelson, Auerbach, Fig.…”
Section: Discussionmentioning
confidence: 85%
“…For example, Siegle and colleagues found that patients who exhibited greater sustained amygdalar responses in the aftermath of negative stimuli displayed greater improvement following cognitive-behavioral therapy 19 . Because amygdalar response to emotionally salient stimuli is thought to be a transdiagnostic marker of internalizing disorders 20,21 and prominent clinical phenotypes of anxiety involve protracted forms of attention (e.g., worry) 22,23 , it is possible that sustained amygdalar response in the aftermath of emotional stimuli could also be utilized to predict the effectiveness of interventions for anxiety, such as ABM.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, those with GAD (vs. controls) were more likely to report that worry created and sustained negative emotion (Llera & Newman, 2017). Trait worry was also associated with sustained hypervigilance to threatening stimuli at a neural level (Burkhouse, Woody, Owens, & Gibb, 2015).…”
mentioning
confidence: 99%